2017
DOI: 10.1016/j.fsi.2016.11.060
|View full text |Cite
|
Sign up to set email alerts
|

Long-term organic selenium supplementation overcomes the trade-off between immune and antioxidant systems in pacu ( Piaractus mesopotamicus )

Abstract: Selenium (Se) is an essential nutrient for antioxidant defenses in fish because of its role in preventing immunosuppression caused by oxidative stress. In this study it was demonstrated the relation between the oxidative stress and immune status after a long Se supplementation period, as a result of the evaluation of immunological, hematological and antioxidant responses, as well as growth performance of pacu fed diets supplemented with different concentrations of organic selenium (0, 0.3, 0.6, 0.9, and 1.8 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 41 publications
2
29
0
1
Order By: Relevance
“…This is in agreement with results from other studies. The growth parameters (final average weight, WG and SGR) of the loach Paramisgurnus dabryanus (Sauvage) were not significantly affected by diet Se‐chitosan (Victor et al, ), and the growth performance of pacu ( Piaractus mesopotamicus ) was not significantly affected by different levels of Se‐yeast in diet (Takahashi et al, ). And the decreased growth rate in fish fed diet with 0.3 mg/kg Nano‐Se can be explained by the significantly reduced intraperitoneal fat and lipid content in hepatopancreas (not shown data), and this effect of Se on lipid accumulation has been reported by previous study (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with results from other studies. The growth parameters (final average weight, WG and SGR) of the loach Paramisgurnus dabryanus (Sauvage) were not significantly affected by diet Se‐chitosan (Victor et al, ), and the growth performance of pacu ( Piaractus mesopotamicus ) was not significantly affected by different levels of Se‐yeast in diet (Takahashi et al, ). And the decreased growth rate in fish fed diet with 0.3 mg/kg Nano‐Se can be explained by the significantly reduced intraperitoneal fat and lipid content in hepatopancreas (not shown data), and this effect of Se on lipid accumulation has been reported by previous study (Liu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Fish antioxidant capacity depends, in part, on dietary supply of essential antioxidants, such as Se and vitamin E (Küçükbay et al, ; Liu et al, ; Trenzado et al, ). It is reported that antioxidant supplementation reduces oxidative stress and improves the immune functions of fish (Takahashi et al, ). Selenium and vitamin E act as biological antioxidants to protect cellular membranes from oxidative damage (Rotruck et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Selenium as a component of glutathione peroxidase (GPx) and thioredoxin, which decompose hydroperoxide radicals, directly protect the cellular membranes from oxidative damage (Bell, Cowey, Adron, & Shanks, ; Biller‐Takahashi et al, ; Rotruck et al, ). Adequate levels of selenoproteins such as GPx and thioredoxin are particularly important for maintaining proper immune response (Arthur, McKenzie, & Beckett, ; Takahashi et al, ). This nutrient also plays an important role in preventing the immunosuppressive action of oxidative stress (Biller‐Takahashi et al, ; Hoffmann, ), and this is important particularly under intensive fish culture, which stress could lead to immunosuppression and may experience significant losses from diseases (Takahashi et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that Se-yeast roughly contained 700-900 mg/kg selenomethionine in its selenocompounds (Block et al, 2004;Ip et al, 2000). As an excellent organic Se product, Seyeast has been extensively studied as a Se supplement in the feeds of various animals, such as lambs (Juniper, Phipps, Ramos-Morales, & Bertin, 2009;Vignola et al, 2009), goats (Shi et al, 2011), pigs (Pinto et al, 2012;Zhao et al, 2016), chickens (Ahmad et al, 2012;Wang & Xu, 2008) and fish (Ozluer-Hunt et al, 2011;Liu et al, 2017;Takahashi et al, 2017).…”
mentioning
confidence: 99%